Simone de Beauvoir e a libertação da mulher: do existencialismo sartriano à moral da ambiguidade. - Seus, Beatrís da Silva (2019)
The present work consists of an analysis from the structural point of view of Simone de Beauvoir‟s and Jean-Paul Sartre‟s thought, delimited by the main works: The Second Sex; Moral of Ambiguity; Being and Nothingness and Existentialism is a Humanism. The guiding thread of this analysis is to demonstrate that the most plausible answer to the problem of women's liberation, proposed by Beauvoir in her genealogy of woman, can be elaborated through the joined understanding of both authors. This is because the philosopher in question not only revisits the notion of human nature found in the ontological and phenomenological work of Sartre, but also gives continuity to his unfinished moral treatise. Thus, it will be observed not only the way in which the thoughts of both philosophers are structured, but also as a feminist problem, it may have not only a political solution, but also a philosophical one from the point of view of criticism and grounding of a new morality. This research also contributes to the fact that The Second Sex, which has been studied in several lines of thought and diverse areas of knowledge for many years, has as its starting point the existentialist and atheist humanist method of the aforementioned authors, and cannot then be analyzed in a purely literary way without first, a deepening of what would be the philosophies of the authors in question. We will therefore be reading both authors in search of a relation that facilitates Beauvoir's understanding of the world in The Second Sex, especially at the end of the work, which can be misunderstood if one lacks the understanding of her works in moral philosophy. To facilitate this approximation, we will be in this dissertation presenting what would be the problem of the liberation of woman according to Beauvoir, and her commitment with the figure of the Other; then we will analyze the ontological and phenomenological work of Sartre to understand how the philosopher recovers this theory, so that in the end we can understand how the author reiterates the moral character of this Sartrian vision and places it in an often implicit way in what we call its genealogy of the female sex.